Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fendo.2021.691736
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Thyroid Hormones on Thyroid Cancers

Abstract: L-Thyroxine (T4) is the principal ligand of the thyroid hormone analogue receptor on the extracellular domain of integrin αvβ3. The integrin is overexpressed and activated in cancer cells, rapidly dividing endothelial cells, and platelets. The biologic result is that T4 at physiological concentration and without conversion to 3,3’,5-triiodo-L-thyronine (T3) may stimulate cancer cell proliferation and cancer-relevant angiogenesis and platelet coagulation. Pro-thrombotic activity of T4 on platelets is postulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Integrative analyses revealed that integrin-mediated pathways are at the nexus of crosstalk between blood and tumor, and complement activation and coagulation cascades at the circulating level may promote tumor growth. This finding adds to recent discussions on the roles of thyroid hormones (THs) in thyroid cancer proliferation, metastasis, angiogenesis, and radio-resistance via integrin, which is overexpressed in cancer cells [ 40 ]. Additionally, the human complement system consists of approximately 50 serum proteins and membrane-bound regulators and receptors [ 41 ].…”
Section: Discussionsupporting
confidence: 58%
“…Integrative analyses revealed that integrin-mediated pathways are at the nexus of crosstalk between blood and tumor, and complement activation and coagulation cascades at the circulating level may promote tumor growth. This finding adds to recent discussions on the roles of thyroid hormones (THs) in thyroid cancer proliferation, metastasis, angiogenesis, and radio-resistance via integrin, which is overexpressed in cancer cells [ 40 ]. Additionally, the human complement system consists of approximately 50 serum proteins and membrane-bound regulators and receptors [ 41 ].…”
Section: Discussionsupporting
confidence: 58%
“…57,58 L-Thyroxine can stimulate cancer cell proliferation, cancerrelevant angiogenesis, and platelet coagulation. 59 Therefore, lifestyle and genetic factors may have a joint influence on TC by controlling the changes in thyroid hormones. In addition, the interaction between a high PRS and an unfavorable lifestyle showed no significance at an additive and multiplicative scale, which might partly be due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…T3 is an important regulator of androgen signaling, and more specific studies must be performed to discriminate between androgen-dependent and independent mechanisms. TH effects on cancer progression seem to be divergent and depend on the tumoral environment ( 51 , 75 ). As previously reviewed, THs exert dual actions.…”
Section: General Discussion and Perspectivesmentioning
confidence: 99%